Association between maternal single-nucleotide polymorphisms in HLA-G gene and risk of preeclampsia. (12th December 2022) - Ma, Cui; Zheng, Yuanyuan; Liu, Xiaowei; Zhang, Weiyuan
Abstract: Aim: To determine the relationship between the maternal single-nucleotide polymorphisms (SNPs) in human leukocyte antigen G (HLA-G) gene and preeclampsia (PE), so as to provide guidance for the early risk prediction of PE. Methods: From October 2017 to October 2019, a total of 99 pregnant women were enrolled in this cross-sectional study. The PE group included 51 pregnant women with severe PE, and the control group included 48 pregnant women with normal delivery during the same period. DNA was extracted and the SNPs in HLA-G gene of the two groups were sequenced. Maternal SNPs in HLA-G gene affecting the occurrence of the PE were determined. Results: In this study, patients with PE had increased gravidity ( p = .002), increased BMI before delivery ( p = .004), reduced neonatal weight ( p < .001), reduced gestational weeks ( p < .001), reduced placental weight ( p < .001), and increased proportion of cesarean section ( p < .001). There were significant differences in SNPs at locus 29794467, 29796376, and 29799440 between the two groups ( p < .05). In locus 29799440, patients with genotype CC had a lower risk of PE than patients with genotype TT ( p = .047), with an odds ratio (OR) of 0.347(95%CI: 0.031, 3.881). And there was no significant difference in the risk of PE between patients with genotype CT, and those with genotype TT ( p = .090) (OR = 2.344 95%CI: 0.187, 29.344) Conclusion: There is an association between a SNP in locus 29799440 of the HLA-G gene and susceptibility of PE in Han Chinese pregnant women, and the risk of PE increases with genotype CT/TT in pregnant women.